An Excerpt from Twelve Hours of Light, Twelve of Darkness - Leech, Angus (UnderCurrents: Journal of Critical Environmental Studies, 1999)
We skittered across landscapes like rocks across pavement, leaving only chalky marks behind to mark our passage, taking with us from each point of contact only a small scar that becomes invisible when wet. [...]